Exploring the potential of ChatGPT for foreign language education at the university level - Klimova, Blanka; Pikhart, Marcel; Al-Obaydi, Liqaa Habeb (Frontiers in Psychology, 2024)
Introduction The purpose of this study is to explore students’ attitudes and perceived usefulness of using ChatGPT for learning a foreign language to reveal how this new trend tool affects its end-users. Methods The authors conducted qualitative research by using a questionnaire survey based on hands-on experience by university students. Results The findings reveal that students are fascinated, satisfied, and stimulated to use this technology despite some of their reservations and potential threats. The authors of this study also list pedagogical implications, including specific activities, while using ChatGPT. Discussion Although ChatGPT can be very beneficial for teachers and help them in their preparation, it sets a challenging task for them to change the existing teaching approaches and assessments to boost students’ cognitive, creative, and critical thinking skills. In addition, both teachers and students will have to upskill their competencies to handle the current advancements in AI technology, such as ChatGPT.